Research hotspots and trends in post-stroke dysphagia: a bibliometric analysis - Xu, Fangyuan; Bai, Lin; Dai, Ziliang; Cheng, Hongliang (Frontiers in Neuroscience, 2023)
Background: Dysphagia represents one of the common complications following a stroke, and post-stroke dysphagia (PSD) can lead to aspiration, pneumonia, and malnutrition, thus prolonging hospital stay, escalating medical expenditures, and imposing a substantial economic strain on both patients and society. The utilization of bibliometric analysis offers a quantitative approach for investigating the existing literature and recognizes the current status of the research. However, bibliometric analysis on the subject of PSD remains absent. Consequently, we carried out this study to provide researchers with insights, facilitating their further exploration of PSD.: Conducting a bibliometric analysis of articles pertaining to PSD retrieved over the past two decades enables us to acquire the research hotspots and trends in this area. The publications concerning PSD were searched from the Core Collection of Web of Science, spanning the period ranging from 2003 to 2023. Articles or reviews published in English were included in this study. Subsequently, we employed CiteSpace and VOSviewer software to visualize the retrieved articles, thereby identifying the cooperative relationships of authors, institutions, and countries, as well as relevant information about journals and references.Results: This study comprised 866 papers in total, and the number of articles published each year shows an overall growth trend. As for the analysis of authors, Dziewas R was the most prolific author with 21 articles. The most frequently published institutions, countries, and journals were the University of Manchester, China, and Dysphagia, with 28, 254, and 75 publications, respectively. And the co-cited authors and journals with the highest counts were Martino R and Stroke.According to the analysis of keywords and references, dysphagia screening and assessment, prevention of pneumonia, rehabilitation approaches, and nutritional management of PSD are considered research hotpots. Additionally, future research may focus on the topics of systematic review and meta-analysis, noninvasive brain stimulation, and lesion location.Through the bibliometrics analysis of PSD, we can capture the research hotspots and frontiers of PSD, thereby providing inspiration and reference for subsequent studies in this field.